The Essence of Philosophy: Definition, Branches and Functions - Ai Nurmaya Juwaenah; Maspuroh, Maspuroh; Aulia Fazri Silmi; Isan Sanusi (Penerbit Hellow Pustaka, 2026)
Since ancient times, philosophy has been recognized as the mother of all sciences because it serves as the foundation for rational, systematic, and critical thinking in understanding reality. Philosophy arises from human curiosity about oneself, nature, and God, seeking answers to fundamental questions about truth and the meaning of life. Through its development, philosophy has given birth to several branches of knowledge, including ontology (the nature of being), epistemology (the sources and methods of knowledge), and axiology (the values and purposes of knowledge). Great thinkers such as Pythagoras, Socrates, Plato, and Aristotle have contributed to shaping philosophical thought that underlies modern science. In practice, philosophy functions to develop critical and reflective thinking, cultivate wisdom, and provide ethical foundations for various aspects of life such as education, social and political systems, science, and religion. By understanding philosophy, humans are able to structure their thinking logically and use knowledge as a means to pursue truth and virtue.